Enterprise 2.0 Technologies for Knowledge Management: A Study of Cultural, Organizational and Technological Factors - AlMohsen, Dina Saad (Université d'Ottawa / University of Ottawa, 2013)
In the new business world, organizational knowledge is considered to be a key factor for profitability attainment. This is true within any industry. It is a vital enabler of superior business accomplishments and developments. Managing such valuable knowledge enables organizations to gain a competitive advantage and advance in the process of wealth creation. As organizations worldwide become increasingly aware of the benefits that can be achieved by engaging in effective knowledge management practices, the need arises for additional research in order to identify and ascertain the effects of cultural differences among the operating environments of different firms, and to find out how these differences translate into varying uses of technologies and knowledge management practices in firms; that is the main objective of this research. To reach this goal, the study utilizes an exploratory research design to collect and analyze quantitative data from employees of various organizations in different countries and industries. We do this in order to explore the determinants of effective knowledge management from cultural, organizational, and technological perspectives. Specifically, the study will examine the country of Saudi Arabia and compare it to other countries. Quantitative data for an empirical investigation was collected through a web-based survey questionnaire sent to employees of various organizations within different national contexts and industrial settings. Drawing upon previously validated studies and several new hypotheses, this study presents a theoretical model that integrates different sociological and technological factors that influence employees’ behavior when using Enterprise 2.0 technologies for knowledge management. Sociological determinants include: power distance, long term-orientation, knowledge management environment, and personal and organizational behavior. The technological determinants include: Enterprise 2.0 tools, richness, sophistication, ease of use, usefulness and behavioral intention of really using these tools. The quantitative investigation reflects the testing of significant theoretical constructs and relational propositions from the theoretical model. Exploratory factor analysis and structural equation modeling techniques were used to estimate a structural relationship model among the sociological and technological determinants of the intentions of use of Enterprise 2.0. The key findings from this study emphasize the role of technology perceptions including: perceived ease of use, perceived usefulness, richness, sophistication of adoption, the use of Enterprise 2.0 technologies in the workplace, as well as the knowledge management environment of the organization. Furthermore, the results highlight the impact of factors pertaining to knowledge management, such as personal and organizational information on the use of Enterprise 2.0 tools. This study also found that divergences among countries with different cultural settings might affect the knowledge management environment and the use of Enterprise 2.0 in organizations; further investigation is needed in this area. Based on these findings, the study offers theoretical implications and suggestions for future research. This research provides guidelines for practices, processes, and technologies related to knowledge management. It also gives specific recommendations, for companies operating in various cultural contexts, on how to give priority to the context and the environment in which the knowledge is being exchanged as well as how to enhance the technological infrastructures that offer a behavioral incentive to use Enterprise 2.0 technologies for knowledge management.
Keywords: enterprise 2.0; knowledge management; Web 2.0; national culture; organizational culture; technology